Den kritiske fase Innvandring til Norge fra Pakistan 1970-1973 - Korbøl, Aud (Scandinavian University Press (Universitetsforlaget), 2022)
Aud Korbøl's «The critical phase. Immigration to Norway from Pakistan» from 1973 is a pioneering work in Norwegian migration research and was published for the first time in book form in 2018. The analyses are based on statistical material and extensive fieldwork among the first Pakistani labour migrants who came to Norway in the early 1970s. The book gives an insight into the Norwegian society at the time, the Pakistani society in which the labour migrants left, the struggle to find work and housing, and how the Pakistani family and kinship system influenced the migrants' adaptation process in Norway. The title alludes to the fact that the period Korbøl describes was a critical phase for the Norwegian authorities, for the Pakistani migrant workers, and for Korbøl herself. Yet, the title also suggests that movement across national borders has costs for individuals' personal, social, and cultural identities. The critical phase is thus an inextricable feature of the migration process and just as relevant today.